Review of influential clinical factors in reducing the risk of unsuccessful MRI-guided HIFU treatment outcome of uterine fibroids - Duc, Nguyen Minh (Diagn Interv Radiol, 2018)
Magnetic resonance imaging-guided high-intensity focused ultrasound (MRI-guided HIFU) is an effective noninvasive treatment option for symptomatic uterine fibroids. However, tissue characteristics of uterine fibroids and technical limitations can limit the patient population that can benefit from this therapy. In this article, we present our literature review focusing on the influential clinical factors that might reduce the risk of an unsuccessful MRI-guided HIFU treatment outcome of uterine fibroids.